2020
DOI: 10.1136/bmjinnov-2020-000447
|View full text |Cite
|
Sign up to set email alerts
|

Drug poisoning management using smartphones: an apps review study based on use case classification model

Abstract: Drug poisoning is the most common form of poisoning in the world. Timely and efficient management of this form of poisoning may save the life of many patients. Today, smartphone apps are widely used for various utilisations, such as for medical purposes. This study aimed to review the crucial characteristics of Android and iOS apps for drug poisoning management and categorise them by the use case classification model. Google Play and App Store were searched in December 2018 for drug poisoning apps usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 13 publications
1
1
0
Order By: Relevance
“…About half of the apps (20/49, 41%) required payment to access all the content, with a cost ranging from €0.59 (US $0.64) to €179.99 (US $196.10). This is a similar percentage than that observed in a recent study on drug poisoning management apps [ 42 ]. Nevertheless, it is considerably higher than that observed in other recent reviews of apps for medical emergencies [ 8 ], medication management and adherence for patients [ 28 , 32 ], or checking for drug-drug interactions [ 36 ].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…About half of the apps (20/49, 41%) required payment to access all the content, with a cost ranging from €0.59 (US $0.64) to €179.99 (US $196.10). This is a similar percentage than that observed in a recent study on drug poisoning management apps [ 42 ]. Nevertheless, it is considerably higher than that observed in other recent reviews of apps for medical emergencies [ 8 ], medication management and adherence for patients [ 28 , 32 ], or checking for drug-drug interactions [ 36 ].…”
Section: Discussionsupporting
confidence: 85%
“…Very recently, a study identified 23 drug reference apps with local drug information in Taiwan (including those aimed at both patients and professionals) and analyzed their quality and factors influencing user perceptions [ 41 ]. In the field of emergency care, a recent study analyzed apps for the management of drug poisoning [ 42 ]. Of the 17 apps identified, 14 (82%) presented diagnosis and treatment guides, and 3 (18%) were specifically on antidotes and their dosage.…”
Section: Discussionmentioning
confidence: 99%